2016
DOI: 10.1159/000446270
|View full text |Cite
|
Sign up to set email alerts
|

The Paris System for Reporting Urinary Cytology: The Quest to Develop a Standardized Terminology

Abstract: The main purpose of urine cytology is to detect high-grade urothelial carcinoma (HGUC). With this principle in mind, The Paris System (TPS) Working Group, composed of cytopathologists, surgical pathologists, and urologists, has proposed and published a standardized reporting system that includes specific diagnostic categories and cytomorphologic criteria for the reliable diagnosis of HGUC. This paper outlines the essential elements of TPS and the process that led to the formation and rationale of the reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
284
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(289 citation statements)
references
References 47 publications
3
284
2
Order By: Relevance
“…However, it was determined that with SPIDs, patient management was changed in 11.04% (19) of the cases in comparison to microscopic diagnoses. [17][18][19][20] ( Table 4). This result indicated that it was risky to make a primary diagnosis with SPIs in telecytology.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was determined that with SPIDs, patient management was changed in 11.04% (19) of the cases in comparison to microscopic diagnoses. [17][18][19][20] ( Table 4). This result indicated that it was risky to make a primary diagnosis with SPIs in telecytology.…”
Section: Discussionmentioning
confidence: 99%
“…It proposes 7 diagnostic categories, arising from a worldwide consensus [12,13] . It is a semiquantitative interpretation of urine samples that relies heavily on increased N/C ratios and on a combination of varying degrees of hyperchromasia, nuclear membrane irregularity and coarse irregular chromatin to arrive at the diagnosis of atypia, suspicious or high-grade urothelial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The visualization of tumors during cystoscopy and ureteroscopy is considered the gold standard method of detection but is an invasive procedure that is time-consuming, costly, and uncomfortable for the patient. Urinary tract cytology (UTC) is a useful, noninvasive adjunct for surveillance because of its high specificity for the detection of high-grade urothelial carcinoma (HGUC) [3, 4]. Unfortunately, UTC has limited sensitivity for the detection of HGUC and poor sensitivity and specificity for the detection of low-grade urothelial neoplasms, such as low-grade urothelial carcinoma (LGUC) [5, 6].…”
Section: Introductionmentioning
confidence: 99%